Find all functions that satisfy: Then the function is a function.
Bonus: Investigate some properties of the function
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let us first examine the nature of the function. Let x = y = 0 : f ( 0 ) 2 = f ( 0 ) 2 + f ( 0 ) 2 ,which implies that f ( 0 ) = 0 .
Now let y = − x : f ( x − x ) 2 = f ( 0 ) 2 = f ( x ) 2 + f ( − x ) 2
But,the square of a real number is always non-negative and 2 squares,when summed,can produce 0 iff each square(and thus the number squared) is 0.That is, f ( x ) = f ( − x ) = 0 ,so, f ( x ) 2 + f ( − x ) 2 = 0 2 + 0 2 = 0 .
Let us gather what we have obtained : − ( 1 . ) f ( 0 ) = 0 ( 2 . ) f ( x ) = 0 and, ( 3 . ) f ( − x ) = 0 This can be evidently achieved iff f ( x ) = 0 for all real x . So it is a constant function.